Preliminary Evidence That High-Dose Vitamin C has a Vascular Disrupting Action in Mice - Baguley, Bruce C.; Ding, Qi; Richardson, Emma (Frontiers in Oncology, 2014)
High intravenous doses of vitamin C (ascorbic acid) have been reported to benefit cancer patients but the data are controversial and there is incomplete knowledge of what physiological mechanisms might be involved in any response. Vitamin C is taken up efficiently by cells expressing SVCT2 transporters and since vascular endothelial cells express SVCT2, we explored the hypothesis that administration of high dose vitamin C (up to 5 g/kg) to mice might affect vascular endothelial function. A single administration of vitamin C to mice induced time- and dose-dependent increases in plasma concentrations of the serotonin metabolite 5-hydroxyindole acetic acid (5-HIAA), a marker for vascular disrupting effects. Responses were comparable to those for the tumor vascular disrupting agents vadimezan and fosbretabulin. High-dose vitamin C administration decreased tumor serotonin concentrations, consistent with the release of serotonin from platelets and its metabolism to 5-HIAA. High-dose vitamin C also significantly increased the degree of hemorrhagic necrosis in tumors removed after 24 hours, and significantly decreased tumor volume after 2 days. However, the effect on tumor growth was temporary. The results support the concept that vitamin C at high dose increases endothelial permeability, allowing platelets to escape and release serotonin. Plasma 5-HIAA concentrations could provide a pharmacodynamic biomarker for vitamin C effects in clinical studies.